A lifestyle intervention during pregnancy to reduce obesity in early childhood: the study protocol of ADEBAR - a randomized controlled trial - Nina Ferrari; Laura Schmitz; Nikola Schmidt; Esther Mahabir; Patricia Van de Vondel; Waltraut M. Merz; Walter Lehmacher; Stephanie Stock; Konrad Brockmeier; Regina Ensenauer; Tanja Fehm; Christine Joisten (BMC, 2020)
Abstract Background The prevalence of obesity in childhood is increasing worldwide and may be affected by genetic factors and the lifestyle (exercise, nutrition behavior) of expectant parents. Lifestyle factors affect adipokines, namely leptin, resistin, and adiponectin as well as cytokines such as tumor necrosis factor alpha (TNF-α) and interleukin-6 (IL-6), which are involved in the regulation of maternal metabolic homeostasis, glucose metabolism, and the development of insulin resistance, metabolic syndrome, gestational diabetes mellitus, and hypertension. However, studies focusing on the effect of exercise or a combination of parental exercise and nutrition on the above-mentioned markers in newborns (venous cord blood) and especially on the long-term development of infants' weight gain are lacking. The study will investigate the effects of a multimodal intervention (regular exercise, diet) on parental and childhood adipocytokines (leptin, resistin, adiponectin, TNF-α, IL-6, BDNF). The effect of a lifestyle-related change in "fetal environmental conditions" on the long-term weight development of the child up to the age of two will also be assessed. Methods/design A randomized multi-center controlled trial will be conducted in Germany, comparing supervised aerobic and resistance training 2x/week (13th to 36th weeks of gestation) and nutritional counseling (6th to 36th weeks of gestation) during pregnancy with usual care. Thirty women (pre-pregnancy Body Mass Index ≥25 kg/m2, 6th-10th week of gestation) will be included in each group. Maternal anthropometric and physical measurements as well as blood sampling will occur at the 6th-10th, 13th-14th, 21st-24th, and 36th week of gestation, at delivery as well as 8 weeks and 24 months postpartum. Neonatal measurements and umbilical blood sampling will be performed at birth. Maternal and infants' weight development will be assessed every 6 months till 24 months postpartum. A difference in childhood BMI of 1 kg/m2 at the age of two years between both groups will be assumed. A power size of 80% using a significance level of 0.05 and an effect size of 1.0 is presumed. Discussion A better understanding of how lifestyle-related changes in the fetal environment might influence infants' outcome after two years of life could have a profound impact on the prevention and development of infants' obesity. Trial registration The trial is registered at the German Clinical Trial Register ( DRKS00007702 ); Registered on 10th of August 2016; retrospectively registered https://www.drks.de/drks_web/navigate.do?navigationId=trial.HTML&TRIAL_ID=DRKS00007702